Budget (Henry Stewart Talks, 2025)
Budget Definition and Purpose, Budgets vs. Financial Statements, Personal vs. Organisational Budgets, Benefits of Budgeting, Types of Budgets, Cash Budgets and Liquidity Management, Budget Participation and Involvement, Budgets in the Public Sector, Government Budgeting and Public Debt, Impacts of Government Budget Strategies